Chapter 3. Quality-by-Design in Pharmaceutical Development (Computer Aided Drug Development, 2024)
AuthorMr. Sri Venkatesh UritiAssociate Professor, Department of Pharmacology, Sri Sivani College of Pharmacy, Chilakapalem Junction, Srikakulam, Andhra Pradesh, IndiaAbstractQuality-by-Design (QbD) represents a paradigm shift in pharmaceutical development, emphasizing systematic and science-based approaches to product and process understanding. The exploration of ICH Q8 guidelines provides fundamental principles for implementing QbD in pharmaceutical manufacturing. QbD emerges as a crucial framework for ensuring product quality through systematic development approaches rather than relying solely on end-product testing through examination of regulatory and industry perspectives, along with practical applications. The integration of regulatory requirements with scientific methodologies demonstrates how QbD principles can be effectively implemented to enhance product quality, reduce variability, and streamline the approval process. Real-world applications illustrate the practical implementation of QbD principles across various pharmaceutical development scenarios, showcasing its value in modern pharmaceutical manufacturing.Keywords: Quality-by-Design (QbD); ICH Q8 guideline; Pharmaceutical development; Regulatory compliance; Design space; Risk assessment; Process understanding; Quality attributes; Process controlView PDF